Physical-thermal isolation strategies for the design of sustainable ceramic building units (2020)
The architectural envelope constitutes more than the aesthetic expression of the building, currently it represents one of the most important challenges in the configuration of energy efficiency in buildings, the materials that build this skin are responsible for the energy flows that enter the built space, an aspect that becomes especially relevant in tropics climates with warm temperatures up to 33 °C; From this context, the design as an innovation tool allows the configuration of strategies to grant physical properties to the construction units capable of reducing heat transfer through the optimization of its components. Within this investigation, the addition of passive cooling strategies in ceramic pieces designed with sustainable principles is analyzed. As a methodology, thermal simulations are carried out by finite element method considering a thermal conductivity of a ceramic of 0.407 W/m•k applied to three pieces with thermal insulating design to analyze the comparative results in relation to the behavior of temperature distribution and heat flow. This paper presents the results of applying design criteria in innovative pieces for masonry enclosures from the perspective of sustainability based on the thermal properties of a vernacular material, clay, in the Norte de Santander, Colombia.